Analyzing the Role of Entrepreneurial SCM Competence, Supply Chain Strategies, Family Environment and Entrepreneurial Motivation towards Entrepreneurial Intentions - Widodo, Djoko Setyo (International Journal of Supply Chain Management, 2020)
The current study purpose is to figure out the interrelationship among the family environment, entrepreneurial motivation, entrepreneurial supply chain management competencies, supply chain strategies and entrepreneurial intention of students in at Krisnadwipayana university of Jakarta. For this purpose, the data was collected from the 300 students of Krisnadwipayana university of Jakarta that represent 50 percent response rate. Using cross sectional research design and quantitative research approach. The Structural Equation moderating (SEM) technique direct effect key findings had shown that family support had a significant relationship with the entrepreneurial intention, while entrepreneurial intention did not have a direct relationship with the entrepreneurial motivation. The direct effect further shown that entrepreneurial motivation, supply chain strategies also have a significant relationship with the EI. Similarly, entrepreneurial supply chain management competencies also had a positive and significant relationship with the supply chain strategies. In other words, the indirect effect had shown that entrepreneurial motivation also significantly mediating in the relationship of family environment and entrepreneurial intention. Moreover, the entrepreneurial supply chain management competencies also positively and significantly moderated on the family support and entrepreneurial motivation. These findings could add a body of knowledge that could provide help to increase the future research. The research limitations were also discussed at the study end.